ARBUSCULAR MYCORRHIZAL FUNGI ASSOCIATED WITH Calycophyllum spruceanum (CAPIRONA) IN THE PERUVIAN AMAZON - ROJAS MEGO, Krystel Clarissa (2024)
Arbuscular mycorrhizal fungi (AMF) play an important role in ecological restoration, enhancing the establishment of native tree species and agricultural crops. The present study aimed to determine the diversity and distribution of AMF species in capirona (Calycophyllum spruceanum Benth.) that was planted at different times in areas of the department of Ucayali, Peru. Samples were taken from the rhizospheres of this plant in the localities of Yarinacocha (YC), Curimaná (CM), Irazola (IZ), Alexander von Humboldt (VH) and the AMF species were identified. The YC sampling zone, with one year old plants, recorded the highest number of spores (20 spores per g of dry soil) in relation to the 18 year old plantations at VH, CM, IZ with 4, 4 and 3 spores per g of soil. A total of 45 AMF species were identified, finding the greatest diversity in the VH sampling zone with 21 species, followed by the CM and YC sampling zones with 17 and 16 species, and at IZ having only 13 species. The three families Acaulosporaceae, Diversisporaceae and Glomeraceae together were represented with 11, 14, 12, and 17 AMF species for YC, CM, IZ, VH. The lower species number at YC and IZ corresponded with the higher concentration of phosphorus in the soils. It appears that capirona forms a rapid symbiosis with the native AMF population, and there might be no need to think of a strategy of inoculating seedlings with a commercial AMF inoculum.